(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of a resident nurse in orthopedics and traumatology, addressing the importance of integration by professionals, focused on multidisciplinary care. Methodology: This is an experience report, with a descriptive character and with a qualitative approach. Results: From the experience in the multiprofessional orthopedic residency, it was evidenced how each professional has their role in the context of care practices and how their work together influences the patient’s prognosis, even in the face of little opportunity for professionals to work and interact with each other. others in a teaching and learning process. Final Considerations: Therefore, at the end of the work, it was identified how the multiprofessional residency in health favors the development of skills and constant learning by the resident, where he can perform his role in a team and in an interdisciplinary way, valuing each area of ​​work, even in the face of limitations that affect their communication and highlight the individualism of the professions, being necessary to emphasize the quality of the integral work to the orthopedic patient.